La impunidad de los delitos sexuales a menores y el juzgamiento en ausencia de los infractores. - Hernández Pacheco, Diego Joaquín (2022)
In this research paper, an analysis of the legality of allowing a trial in the absence of the defendant is carried out in cases in which the victims of sexual crimes are children and adolescents. Since the Ecuadorian criminal legal system in the procedural area does not allow a trial in absentia this generates impunity since often the accused, to avoid prosecution and punishment, escape or avoid being located. It is intended, through the correlative method, to make a study of comparative law, especially comparing Ecuadorian legislation with the other countries, as well as with the recommendations of the Directive of the European Union and the Council of the European Union. Emphasizing that in these countries and in the European Union (“EU”), under established budgets, it is possible to judge a person in absentia. These research examples do not allow, to lay theoretical and legal bases to propose reform to numeral 11 of article 563 of the Organic Integral Penal Code. This is the only way to better guarantee the rights and comprehensive reparation of underage children in the case of being victims of sexual crimes, something that should be done since children and adolescents enjoy and should enjoy special protections by the Ecuadorian state.